Composition dependent spectroscopic properties of Er3+‐doped boro‐tellurite glasses. Issue 3 (25th January 2013) - Selvaraju, K.; Vijaya, N.; Marimuthu, K.; Lavin, V.
Abstract A new series of Er3+‐doped boro‐tellurite glasses have been prepared and their spectroscopic behavior were explored through absorption and luminescence measurements. The nature of the Er3+‐ligand bond in the host matrix were studied through bonding parameter studies using absorption spectra. Davis and Mott theory is used to determine the optical band gap energy for the direct and indirect allowed transitions of the title glasses. Optical band gap energy for the indirect allowed transitions are found to be in the range of 3.03–2.36 eV. The Judd–Ofelt intensity parameters Ωλ (λ = 2, 4, and 6) were determined from the absorption spectra and used to derive the radiative properties like stimulated emission cross‐section and gain bandwidth for the emission transition 4I13/2 → 4I15/2 of the Er3+ ions. The spectroscopic properties of the prepared glasses were studied as a function of TeO2 in the host matrix and discussed with reported literature.